Molecular Glue for RNA: Regulating RNA Structure and Function through Synthetic RNA Binding Molecules. (20th September 2019) - Dohno, Chikara; Nakatani, Kazuhiko
Abstract: We introduce the concept of molecular glues for RNA, in which specific RNA‐binding small molecules induce designed structural changes in target functional RNAs, resulting in modulation of the functions. ( Z )‐NCTS is an RNA‐mismatch‐binding small molecule that recognizes 5′‐r(XGG)‐3′/5′‐r(XGG)‐3′ sequences (X=U or A) and acts as a molecular glue for RNA. The binding of ( Z )‐NCTS brings two distinct 5′‐r(XGG)‐3′ domains into contact with each other, and this can result in higher‐order structural changes of target RNAs. We applied ( Z )‐NCTS to induce the formation of a proposed tertiary structure of a ribozyme together with activation of RNA‐cleaving ability. The concept of a molecular glue could inspire new small‐molecule‐based strategies for regulating biological functions: a synthetic small molecule targeting functional RNAs could regulate the RNA structure and function. Abstract : Let′s stick together : We introduce the concept of molecular glues for RNA. Specific RNA‐binding small‐molecule compounds are used to induce particular structural change in target functional RNAs, resulting in modulation of their functions.